Analisis Penerapan Prinsip Dasar Animasi Dalam Animasi “Weathering With You” - Abyan Dhia Pratama (Jurnal Ilmiah Wahana Pendidikan, 2023)
Animation is a collection of moving images that form a sequence of frames, creating motion. Good animation can bring a story to life and leave a lasting impression on viewers. Therefore, Ollie Johnston and Frank Thomas, the individuals behind classic Disney animated films like Sleeping Beauty and Cinderella, created 12 fundamental principles of animation. This research aims to determine whether the Japanese animation titled "Weathering with You" adheres to these basic principles, despite the significant differences between Western and Japanese animation in many aspects. This study adopts a qualitative descriptive approach with analytical, observational, documentary, and communicative verbal literature review methods. The results of this research confirm the presence of several basic principles of animation in the anime "Weathering with You." This finding also answers that as long as it falls under the category of animation, regardless of stylistic and production process differences, the application of basic animation principles is essential.